Analysis of the Curative Effect of Neoadjuvant Therapy on Pancreatic Cancer - Yang, Liqiong; Bai, Yun; Li, Qing; Chen, Jie; Liu, Fangfang; Weng, Xiechuan; Xu, Fan (Frontiers in Oncology, 2021)
The prevalence of pancreatic cancer is increasing sharply recently, which significantly increases the economic burden of the population. At present, the primary treatment of resectable pancreatic cancer is surgical resection, followed by chemothera-py with or without radiation. However, the recurrence rates remain high even after R0 resection. This treatment strategy does not distinguish undetected metastatic disease, and it is prone to postoperative complications. Neoadjuvant therapies, including neoadjuvant chemotherapy and radiotherapy, is being increasingly utilized in borderline resectable as well as resectable pancreatic cancer. This review summarized and discussed clinical trials of neoadjuvant therapy for pancreatic cancer, comparing resection rates, outcome measures, and adverse reactions between neoadjuvant chemotherapy and neo-adjuvant chemoradiotherapy.